PERAN RADIOLOGI FORENSIK DALAM PEMERIKSAAN KASUS TRAUMA TAJAM DI DADA AKIBAT PERKELAHIAN : LAPORAN KASUS BERBASIS ILMIAH - MAHILA, NIUFTI AYU DEWI; ARROZHI, MUHAMMAD YUSUF (LP2MTBM MAKARIOZ, 2024)
A man came to the Emergency Department of PDHI Islamic Hospital Yogyakarta with chest injuries from being stabbed by his sibling. Cases of sharp trauma to the chest often cause emergency medical conditions that require quick and accurate diagnosis to optimize patient care. Cases of sharp trauma associated with violent acts are often the focus in forensic science for the purpose of identification, reconstruction of events and determination of causal factors. Radiography is one of the diagnostic tools commonly used to evaluate injuries to the chest that contribute to evidence in the process of legal investigations.